2023
DOI: 10.3390/inventions8010039
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Type Materials of Grit Blasting on the Corrosion Resistance of S235JR Carbon Steel

Abstract: The aim of this paper is to evaluate the corrosion rate expressed in material loss per unit of time and the surface properties of carbon steel type S235JR blasted with different types of materials (quartz, alumina, and red garnet with a particle size between 60 and 80 mesh (0.25–0.60 mm)). The estimation of corrosion rate was determined by electrochemical methods, such as open circuit potential (OCP), polarization resistance (Rp), corrosion rate (Vcorr), and gravimetric method by immersing the samples in 3.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…PID control is one of the most widely researched methods of control used for controlling the event trigger transportation system. Article [11] also studies the corrosion rate indicated in the material loss per unit of time and the surface characteristics of the carbon steel type S235JR blasted with different types of materials (quartz, alumina, and red garnet with a particle size between 60 and 80 mesh (0.25-0.60 mm)). The corrosion rate was estimated using electrochemical techniques such as the open circuit potential, corrosion rate, polarization resistance, and gravimetric process.…”
mentioning
confidence: 99%
“…PID control is one of the most widely researched methods of control used for controlling the event trigger transportation system. Article [11] also studies the corrosion rate indicated in the material loss per unit of time and the surface characteristics of the carbon steel type S235JR blasted with different types of materials (quartz, alumina, and red garnet with a particle size between 60 and 80 mesh (0.25-0.60 mm)). The corrosion rate was estimated using electrochemical techniques such as the open circuit potential, corrosion rate, polarization resistance, and gravimetric process.…”
mentioning
confidence: 99%